Window on humanity : - Kottak, Conrad Phillip (McGraw-Hill, 2015)
The author includes discussions of ethnicity and nationalism in a global context, as well as of diversity and multiculturalism in North America. This text of book highlights anthropology's increasingly transnational, multilocal, and longitudinal perspectives.